Nutrient addition enhances carbon sequestration in soil but not plant biomass in a coastal shelter plantation in South China. (13th September 2021) - Fan, Yingxu; Wang, Faming; Sayer, Emma J.; Liu, Zhanfeng; Mo, Qifeng; Xu, Xin; Li, Yingwen; Zou, Bi; Li, Yongxing; Zhang, Jingfan; Li, Zhian
Abstract: Casuarina equisetifolia plantations have been widely established along tropical and subtropical coasts, where they act as a windbreak to shelter coastal areas. These shelter plantations also fulfill another important ecosystem service by sequestering large amounts of carbon (C). However, shelter plantations are usually established on nutrient‐poor sand dunes, which may limit tree growth and therefore C sequestration rates. To assess whether fertilization increases the C sequestration of coastal shelter plantations, we conducted a fertilization experiment in a young C. equisetifolia plantation with four treatments: nitrogen addition (+N), phosphorus addition (+P), nitrogen and phosphorus addition (+NP), and controls (CK). We quantified nutrient availability and annual net ecosystem production (NEP) during the key early establishment phase. Fertilization with +N and +P significantly increased ammonium‐N and extractable P in the surface soils and the N and P concentrations of branches, respectively. Surprisingly, the mean growth rate of C. equisetifolia plantations (24.59 ± 0.66 Mg ha −1  yr −1 ) was not affected by fertilization. The mean NEP was 6.18 ± 0.49 Mg C ha −1  yr −1, and there was no difference among fertilization treatments. However, soil organic C significantly increased by 41% and 36% with +N and +P, respectively, but not +NP. C. equisetifolia plantations can sequester large amounts of C in biomass on poor soils without the need for additional nutrients, although fertilization may enhance soil C storage. Considering the potential large planting area, we suggest that coastal C. equisetifolia shelter plantations could be an important nature‐based solution for climate change mitigation in coastal regions.